2020
DOI: 10.1017/s1047951120000311
|View full text |Cite
|
Sign up to set email alerts
|

Lean body mass is the strongest anthropometric predictor of left ventricular mass in the obese paediatric population

Abstract: Background:Indexing left ventricular mass to body surface area or height2.7 leads to inaccuracies in diagnosing left ventricular hypertrophy in obese children. Lean body mass predictive equations provide the opportunity to determine the utility of lean body mass in indexing left ventricular mass. Our objectives were to compare the diagnostic accuracy of predicted lean body mass, body surface area, and height in detecting abnormal left ventricle mass in obese children.Methods:Obese non-hypertensive patients age… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
4
1

Relationship

0
5

Authors

Journals

citations
Cited by 6 publications
(5 citation statements)
references
References 29 publications
1
4
0
Order By: Relevance
“…Our analysis also confirms that scaling to LBM is best accomplished with a coefficient of 0.85 when derived from a reference group with normal body composition. This is in agreement with previous smaller studies which have found an allometric coefficient close of 0.9 (George et al 2009;Giraldeau et al 2015;Krysztofiak et al 2019;Martinho et al 2020;Shea et al 2020) . Compared to other body size metrics, LBM was more strongly associated with LVM and LVEDV and therefore had the lowest coefficient of variation.…”
Section: Discussionsupporting
confidence: 94%
“…Our analysis also confirms that scaling to LBM is best accomplished with a coefficient of 0.85 when derived from a reference group with normal body composition. This is in agreement with previous smaller studies which have found an allometric coefficient close of 0.9 (George et al 2009;Giraldeau et al 2015;Krysztofiak et al 2019;Martinho et al 2020;Shea et al 2020) . Compared to other body size metrics, LBM was more strongly associated with LVM and LVEDV and therefore had the lowest coefficient of variation.…”
Section: Discussionsupporting
confidence: 94%
“…Lean body mass (LBM) or skeletal muscle mass plays a key role in energy metabolism, and the promotion of LBM and muscular strength is always advocated in preventing obesity‐related metabolic abnormalities, as well as geriatric sarcopenia and frailty 1–3 . Elevated blood pressure (BP) and hypertension are major risk factors of several cardiovascular diseases (CVDs), and generate huge health and economic burdens 4–6 . The unfavorable relationship between LBM and hypertension has been found in cross‐sectional studies, while opposite findings were also reported 7–10 .…”
Section: Introductionmentioning
confidence: 99%
“…[1][2][3] Elevated blood pressure (BP) and hypertension are major risk factors of several cardiovascular diseases (CVDs), and generate huge health and economic burdens. [4][5][6] The unfavorable relationship between LBM and hypertension has been found in cross-sectional studies, while opposite findings were also reported. [7][8][9][10] Such inconsistency was probably resulted from the variances of populations, as well as the utilities of different measurements of LBM.…”
Section: Introductionmentioning
confidence: 99%
“…where 𝒒 𝑖 (𝑠) is the basis of the i-th model term at s-th selection iteration. At the first iteration when 𝑠 = 1, the initial basis is selected as 𝒒 𝑖 (1) = 𝝋 𝑖 , 𝑖 = 1,2, … 𝑀. At each step, the significant term can be selected as 𝒒 𝑠 = 𝒒 𝑙 𝑠 (𝑠) ,…”
Section: The Proposed Tsf-narx Modelmentioning
confidence: 99%
“…Body Mass Index (BMI) describes the relationship between the mass and height of human. It is a critical indicator for the medical research and diagnosis, especially in the field of obesity, maturity and heritability [1][2][3]. The conventional measurement of human BMI is derived from the weight and the square of body height.…”
Section: Introductionmentioning
confidence: 99%